Evidence of room temperature ferromagnetism in argon/oxygen annealed TiO2 thin films deposited by electron beam evaporation technique - Mohanty P.; Kabiraj D.; Mandal R.K.; Kulriya P.K.; Sinha A.S.K.; Rath C. (My University, 2025)
TiO2 thin films deposited by electron beam evaporation technique annealed in either O2 or Ar atmosphere showed ferromagnetism at room temperature. The pristine amorphous film demonstrates anatase phase after annealing under Ar/O2 atmosphere. While the pristine film shows a super-paramagnetic behavior, both O2 and Ar annealed films display hysteresis at 300 K. X-ray photo emission spectroscopy (XPS), Raman spectroscopy, Rutherford's backscattering spectroscopy (RBS), cross-sectional transmission electron microscopy (TEM) and energy dispersive X-ray spectroscopy (EDS) were used to refute the possible role of impurities/contaminants in magnetic properties of the films. The saturation magnetization of the O 2 annealed film is found to be higher than the Ar annealed one. It is revealed from shifting of O 1s and Ti 2p core level spectra as well as from the enhancement of high binding energy component of O 1s spectra that the higher magnetic moment is associated with higher oxygen vacancies. In addition, O 2 annealed film demonstrates better crystallinity, uniform deposition and smoother surface than that of the Ar annealed one from glancing angle X-ray diffraction (GAXRD) and atomic force microscopy (AFM). We conclude that although ferromagnetism is due to oxygen vacancies, the higher magnetization in O2 annealed film could be due to crystallinity, which has been observed earlier in Co doped TiO2 film deposited by pulsed laser deposition (Mohanty et al., 2012 [10]). © 2013 Elsevier B.V. All rights reserved.